PERSEPSI MAHASISWA TENTANG KOMPETENSI PEDAGOGIK DOSEN PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UIR PEKANBARU TAHUN AJARAN 2017/2018 - suryanti, suryanti (Jurnal Bioconcetta, 2019)
This study aims to determine students' perceptions of lecturerâ€™s pedagogic competencies of biology education study program fkip-uirpekanbaru academic year 2017/2018. The study is using survey methods, and used questionnaires, observation, interviews and documentation as the instruments. The population of this study were all sixth semester students, there were 5 classes (a, b, c, d, e) with total of 172 students, which 86 of them are become sample of the study with high, medium and low academic capabilities. The results of the 10 pedagogic competency indicators based on academic ability high is 62.67 (good category) on average, based on moderate academic capabilities, the average value is 64.81 (good category), meanwhile, refer to low academic ability the average score is 63.25 (good category), last, the average recapitulation of pedagogic competencies based on both high, medium and low academic capabilities average value is 63.58 (good category). For lecturers who teach less than five years and lecturers who teach more than five years are obtained by good category. It can be concluded that the students' perceptions of lecturerâ€™s pedagogical competence of the biology education program are in good categories. Â